Distribuição dos grupos funcionais de plantas aquáticas em áreas alagadas costeiras do nordeste brasileiro - Macêdo, Joemília Conceição Araújo (2015)
Aquatic plants located in coastal lagoons have functional traits selected by abiotic conditions and related to the history of life, which allowed them to colonization and establishment in these environments. The present study tested the following hypotheses: (1) that the species have a homogeneous pattern of functional traits, resulting in the formation of a few groups; (2) that the limnological variables and soil act as a filter to select those traits and interfere in the distribution of populations in the pond. Thus the functional traits of the species present in a coastal lagoon in northeastern Brazil were analyzed using a sampling transects. Sediment samples were taken and analyzed in the laboratory. The limnology parameters were measured in the field, as well as the depth of the water depth and the occurrence of species away from the margin. Biological data showed formation of two functional groups, supporting the first hypothesis. But the abiotic variables were associated with the distribution of a few people, refuting the latter. Thus we conclude that the community of aquatic plants analyzed is formed by similar traits and abiotic effects are not decisive for the formation of these groups.